2015
DOI: 10.1242/dev.125989
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic gene regulatory pathways in the sea urchin embryo

Abstract: During embryogenesis the sea urchin early pluteus larva differentiates 40-50 neurons marked by expression of the panneural marker synaptotagmin B (SynB) that are distributed along the ciliary band, in the apical plate and pharyngeal endoderm, and 4-6 serotonergic neurons that are confined to the apical plate. Development of all neurons has been shown to depend on the function of Six3. Using a combination of molecular screens and tests of gene function by morpholino-mediated knockdown, we identified SoxC and Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…It is reported that SoxC cells co-express Delta (Wei et al, 2016) and that treatment with DAPT, an inhibitor of Notch signaling, or a Delta morpholino results in the formation of clusters of neurons Wei et al, 2009;Yaguchi et al, 2011). This suggests that Notch signaling occurs subsequent to the final cell division and that the division is asymmetric, at least in the distribution of molecular components.…”
Section: Discussion the Model Of Neurogenesis In The Sea Urchinmentioning
confidence: 99%
“…It is reported that SoxC cells co-express Delta (Wei et al, 2016) and that treatment with DAPT, an inhibitor of Notch signaling, or a Delta morpholino results in the formation of clusters of neurons Wei et al, 2009;Yaguchi et al, 2011). This suggests that Notch signaling occurs subsequent to the final cell division and that the division is asymmetric, at least in the distribution of molecular components.…”
Section: Discussion the Model Of Neurogenesis In The Sea Urchinmentioning
confidence: 99%
“…Neural progenitors in sea urchins and sea stars are identified by expression of the transcription factor SoxC (Cheatle Jarvela et al, 2016;Garner et al, 2016;Mellott, Thisdelle, & Burke, 2017;Wei, Angerer, & Angerer, 2016;Yankura et al, 2013) ( Figure 3). The distribution of cells expressing SoxC provides an indication of the regions that are neurogenic.…”
Section: Asymmetric Division Of Neural Progenitors and Notch Signalingmentioning
confidence: 99%
“…Because apical organs are found in such diverse organisms they offer a potentially homologous metazoan neural structure that is simple enough to dissect at the GRN level. While apical organ territory patterning is relatively well studied and conserved (Range, 2014), the process of neurogenesis that directs an ectodermally derived progenitor cell to progress to a differentiated serotonergic neuron in this territory remains poorly understood in any of these taxa, although recent work has shown a role for soxc in this process (Garner et al, 2015;Wei et al, 2016).…”
Section: Introductionmentioning
confidence: 99%